1991
DOI: 10.1055/s-2007-1003632
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Euthyroid and Hyperthyroid Goiters Independently of Thyrotropin in Patients with Acromegaly

Abstract: The incidence of palpable goiters, the thyroid functional state and thyroid radioisotope uptake was analyzed retrospectively in 80 patients with acromegaly and 80 patients with prolactinomas. 71% of all patients with acromegaly had an enlargement of the thyroid (goiter); 49% of them had diffuse and 39% nodular goiters. The incidence of goiters in patients with prolactinomas from the same iodine deficient geographic region was only 35% (82% diffuse and 18% nodular). 17.5% of acromegalic patients underwent thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 2 publications
8
38
1
1
Order By: Relevance
“…Therefore, higher TSH levels as the sole factor responsible for goiter appears to be an oversimplification [13]. Goiter should be regarded as a complex trait in which genetic susceptibility [13,16], enviromental factors [13], TSH, growth factors [13,17,18], and angiogenic substances [13,19,20] either play a distinct and separate role or act synergistically through complex interaction mechanisms [13]. However, the relative contributions of these factors to the goitrogenic process have yet to be clarified [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, higher TSH levels as the sole factor responsible for goiter appears to be an oversimplification [13]. Goiter should be regarded as a complex trait in which genetic susceptibility [13,16], enviromental factors [13], TSH, growth factors [13,17,18], and angiogenic substances [13,19,20] either play a distinct and separate role or act synergistically through complex interaction mechanisms [13]. However, the relative contributions of these factors to the goitrogenic process have yet to be clarified [13].…”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly, characterised by elevated levels of serum IGF-I, has long been associated with goitre (>70% incidence; Wuster et al 1991). Minuto et al (1989) described a 2-fold increase in immunoreactive IGF-I in patients with MNTG compared with controls, but IGF-I levels were not elevated in goitres associated with Graves' disease.…”
Section: Igfs Their Binding Proteins and Their Receptorsmentioning
confidence: 99%
“…In most acromegalic patients, TSH response to TRH is impaired due to the inhibition by excessive hypothalamic somatostatin, but complete suppression of TSH is rather rare in cases with preserved anterior pituitary functions. Wi ster et al [5] showed that 10 out of 80 patients with acromegaly had thyroid autonomies. Gemsenjager et al [12] reported that some patients with nontoxic multinodular goiter showed no TSH response to TRH, suggested a state of preclinical hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…patients, several abnormalities related to the thyroid and the pituitary-thyroid axis, such as goiter formation, changes in serum thyroid hormone levels and impaired TSH response to TRH, have been described [1][2][3][4][5][6]. In most studies, serum T4i ]T3 and basal TSH levels are found to be normal.…”
Section: In Acromegalicmentioning
confidence: 99%